THE SOCIAL MEANING OF PUBLIC SPACES - Bierwiaczonek, Krzysztof; Stołpiec, Katarzyna (No Limits, 2022)
A town or city is a settlement unit with a predominance of compact buildings and non-agricultural functions, which has urban rights or the status of a town or city granted under separate regulations. Each city and town has its own specificity expressed in history, architecture, urban layout, and the way of life of its inhabitants. Cities and towns are expected to make their spaces aesthetically pleasing, attractive, and diverse, with an interesting blue-green infrastructure. While many of the cities meet these criteria, few people consider how much social significance each of them has.